Structured ternary fluids as nanocrystal incubators for enhanced crystallization control. Issue 44 (2nd November 2022) - Maunder, J. J.; Aguilar, J. A.; Hodgkinson, P.; Cooper, S. J.
Abstract : Crystallization in structured ternary fluids can proceed via higher nucleation rate and slower crystal growth pathways that are impossible to access in normal unstructured solutions. Hence, structured ternary fluids can act as nanocrystal incubators. Abstract : In crystallization from solution, a ubiquitous process in both industry and the natural world, nucleation is usually the rate-determining step, followed by faster crystal growth. Consequently, crystals typically exist in the nm-size range for such limited times that their investigation and manipulation is hindered. Here, we show that, owing to a degree of restricted diffusion, crystallization in structured ternary fluids (STFs) can proceed via higher nucleation rate and slower crystal growth pathways. This enables STFs to act as nanocrystal incubators, with the nanocrystals existing for extended times. We demonstrate that this generates enhanced crystallization control, with the three ambient pressure polymorphs of glycine, the α-, γ- and β-forms, all crystallizing from the octanol/ethanol/water STF, despite the well-known difficulty in crystallizing the slow growing γ-form and the instability of the β-form. The ability of STFs to produce notoriously hard to crystallize polymorphs should make them a versatile tool, ideal for polymorph discovery. This may enable a step change in the current, scatter-gun approach to polymorph screening. Furthermore, we show that aliquots of the nanocrystal-containing fluids can successfully seed metastable solutions. Hence, STFs may ultimately help provide a generic methodology for producing crystals and seed suspensions of any desired polymorph to supersede current targeted crystallization and seeding strategies.